The awareness of healty lifestyle to attract people through website / Hafizuddin Husin - Husin, Hafizuddin (Faculty of Art and Design, 2015)
Lifestyle and its impact on health is a common topic in the minds of every resident in the Conversation on Health in their daily lives. The importance of addressing issues related to incentive and emphasis on healthy behaviors, healthy lifestyles for children and teenagers, smoking, and personal responsibility, has stressed in many discussions and research. Many people expressed concerns related to unhealthy lifestyles and a negative impact on the health care system that is not correct. Many believe that the most fundamental issues related to healthy lifestyle choices is the way life is simplicity, and that everyone has the means to access healthy food, shelter, stable, and education, people will not be able to have access full health, a journey of life, daily routines and well-being. With this incentive aims to promote a healthy lifestyle among the public in order to reduce the rate of obesity is widespread throughout the country. Many people put more emphasis between a healthy lifestyle, including diet, physical activity and personal habits and avoid unhealthy social activities. Some observers have suggested that there is a need to resist the tendency to look at issues of specific diseases and risk factors to look the same. Many people emphasized the need for integration of environment, transport and health. Have agreed on the importance of infrastructure renewal in many communities to address aging facilities. A large number of deaths and unhealthy lifestyle experienced throughout the world today can be prevented. And should be more people need to prioritize mental fitness and health to create a healthier life.